The Impact of Psychological Empowerment on Job Satisfaction and Organizational Commitment Among Nurses - Wahyudin, Ferdic Sukma (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
The paper presents nurse’s perspective on the link between psychological empowerment, job satisfaction, and organizational commitment. Low levels of organizational commitment among nurses in 5 locations Type II Indonesian Air Force hospitals (RSAU) have become a significant challenge in delivering high-quality healthcare services. This study aims to analyze and validate the contributing factors using data collected from questionnaires and absenteeism records from 2020. Using a purposive sampling technique, a total of 362 nurses agreed to participate as respondents and completed the questionnaire. The results indicate that psychological empowerment as an individual characteristic, can affect organizational commitment as an individual outcome, with job satisfaction serving as the mediating mechanism. Therefore, it is advisable for organizations to increase job satisfaction which plays an important mediating role in increasing organizational commitment,. For further research, it is suggested to include parameters related to organizational culture, ability, and nurse’s personalities to gain a more comprehensive understanding.